The Effect of Citric Acid on Performance and Carcass Characteristics of Broiler Chickens - Martin Fik; Cyril Hrnčár; Dávid Hejniš; Emília Hanusová; Henrieta Arpášová; Jozef Bujko (Scientific Papers Animal Science and Biotechnologies, 2023)
The objective of this study was to investigate the effect of dietary citric acid (CA) on the performance and carcass characteristics of broiler chickens. A total of 240 one-day-old Ross 308 broiler chickens were randomly assigned to four groups (n=60) and reared for a period of 42 days. The drinking water of groups 1, 2, 3 and 4 was supplemented with 0%, 0.50%, 1% or 1.50% CA. At the age of 42 days, 10 birds from each group were slaughtered. The results indicated that birds with CA additions were heavier compared with control birds (P<0.05). Feed consumption was improved (P<0.05) in birds of the CA groups. Citric acid supplementation did not have a significant effect (P>0.05) mortality of broiler chickens. We observed higher (P<0.05) breast, liver, gizzard and small intestine percentage in the groups that were added CA. Thick percentage and carcass yield were not affected (P>0.05) by dietary treatments. Significant reduction (P<0.05) in abdominal fat weight was found with increased level of citric acid in drinking water. It may, therefore, be concluded that the addition of 1.50% CA in drinking water has most effective effect in broiler chickens fattening.